(untitled) (Interdisciplinary Journal of Management and Social Sciences, 2021)
Muna, the female protagonist of the epic poem “Muna Madan”, suffers from prejudices. She becomes the victim of patriarchy. Her effort to resist the imposition of masculinity upon her has been useless ultimately. This paper explores how she appropriates the imposition of masculinity and gives consent to her husband to leave for Tibet. While doing so she remains at home nursing his aged mother, waiting, hoping for his safe return that never materializes until she transforms her from her physical state to the spiritual one.